1996
DOI: 10.1115/1.3101966
|View full text |Cite
|
Sign up to set email alerts
|

Compliant Coatings: A Decade of Progress

Abstract: This brief article reviews the important developments in the field of compliant coatings that took place in the past ten years. During this period progress in theoretical and computational methods somewhat outpaced that in experimental efforts. There is no doubt that compliant coatings can be designed to delay transition and to suppress noise on marine vehicles as well as other practical hydrodynamic devices. Transition Reynolds numbers that exceed by an order of magnitude those on rigid-surface boundary layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 53 publications
(65 reference statements)
1
26
0
Order By: Relevance
“…Now, more than 50 years after the initial experiments of Kramer, there is little doubt that compliant coating may delay transition, c.f. e.g., [16]. Reynolds numbers for transition in geometries with compliant coating may exceed corresponding Reynolds numbers for flow within rigid geometries by more than an order of magnitude.…”
Section: Modelling Of Blood Flowmentioning
confidence: 98%
“…Now, more than 50 years after the initial experiments of Kramer, there is little doubt that compliant coating may delay transition, c.f. e.g., [16]. Reynolds numbers for transition in geometries with compliant coating may exceed corresponding Reynolds numbers for flow within rigid geometries by more than an order of magnitude.…”
Section: Modelling Of Blood Flowmentioning
confidence: 98%
“…This work will be described in Sect. 6. We presume that many readers will probably not be very familiar with the various mechanical properties and characteristics of compliant walls.…”
Section: Introductionmentioning
confidence: 97%
“…However, as pointed out by Carpenter et al [2] most of the quantitative estimates contained in Gray's paper have in the meantime been shown to be inaccurate. Nevertheless, over the last twenty years it has also been clearly established, through experimental and theoretical investigations, that wall compliance can suppress the growth of Tollmien-Schlichting (TS) waves in boundary layers leading to substantial delays in the onset of laminar-turbulent transition (for reviews see [2][3][4][5][6][7]. Consequently compliant walls, or compliant coatings, are a viable method for drag reduction in such quasi-2D flow environments.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of such attempts can be found in [1], where most of researches dealt with 'soft' coatings (either a sponge material covered by a thin film or a gel-like substances). It is known that due to the fluid-solid interaction, such soft materials are subject to different instabilities resulting in surface folding and, hence, in drag increase.…”
Section: Introductionmentioning
confidence: 99%